Impact of environment on international joint ventures in Central and Eastern Europe - Haapamäki, Henna (My University, 2009)
Earlier studies have indicated that environment has an impact on international joint ventures, but there is a need to study the topic more deeply. The goal of this study was to analyse the impact of environment on international joint ventures in Central and Eastern Europe. This study formed more precise criteria than earlier studies have had to determine how developed the investment environment of a country is. Using the criteria, host countries of joint ventures were divided into highly, medium and less developed investment environments, and joint ventures established in different environments were studied and compared. The results support earlier studies, but also produce new information about the impact of environment on joint ventures. Data on country environments was collected mainly from EBRD Transition Reports. Joint ventures were studied by analysing surveys conducted in 2002 and 2007 at the University of Vaasa. The respondents of the surveys were representatives of Finnish firms that had established manufacturing joint ventures in Central and Eastern Europe. The results of this study indicate that joint ventures established in different environments vary; there are differences in the motives of investing firms, the resource contribution of partners and the performance of joint ventures. Market seeking seems to be an important motive, particularly in highly developed investment environments, whereas low-cost production seems to be sought more in medium and less developed environments. The less developed the investment environment is, the clearer the division in resource contribution and the more interdependency between the partners, which may encourage firms to maintain their joint ventures. As to performance, joint ventures in a less developed environment seem to have more problems with cost control and efficiency than joint ventures in more developed environments.
Keywords: international joint venture; Central and Eastern Europe; motives; resources; performance; fi=Markkinointi|en=Marketing|; fi=Kansainvälisen yritystoiminnan koulutusohjelma|